Adapting the Ceramics Process with Creative Problem-Solving - Jennifer Fortuna (Scholarworks @ WMU, 2021)
Madeline Kaczmarczyk, a ceramics sculptor based in Rockford, MI, provided the cover art for the Fall 2021 edition of The Open Journal of Occupational Therapy (OJOT). The piece is a wall vase made from clay, luster glaze, and glass beads. Madeline has been creating decorative ceramics for over four decades. In recent years, Madeline has found creative ways to adapt the ceramics process so she can continue creating beautiful works of art. For Madeline, ceramics is more than a means to make a living. This meaningful activity brings focus to her life.